Terrorism studies : a reader - Horgan, John, 1974-; Braddock, Kurt. (New York : Routledge, 2011)
"In an age when there is more written about terrorism than anyone can possibly read in a lifetime, it has become increasingly difficult for students and scholars to navigate the literature. At the same time, courses and modules on terrorism studies are developing at a rapid rate. To meet this challenge, this comprehensive new Reader in Terrorism Studies seeks to equip the aspiring student, based anywhere in the world, with a comprehensive introduction to the study of terrorism. Containing many of the most influential and groundbreaking studies from the worlds leading authorities on terrorism, drawn from several disciplines, and edited by one of the worlds leading experts, John Horgan, this book is the essential companion for the student of terrorism and political violence.Terrorism Studies, which starts with a detailed Introduction on 'Studying Terrorism', is divided into nine sub-sections, each of which has an introduction and guide to further reading. It will be essential reading for undergraduate students of terrorism and political violence, and recommended reading for students of security studies, international relations and political science in general"--
"This book is a comprehensive Terrorism Studies Reader that aims to introduce and guide students through the most important articles on the subject of terrorism and political violence"--
Includes bibliographical references and index.
Keywords: Terrorism; Political violence